Kreativitas Guru dalam Meningkatkan Minat Belajar Siswa dalam Mata Pelajaran Ips Di MAN 4 Kediri - Lailatul Badriyah Sari; Hendra Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted to find out how teacher creativity increases students' interest in learning in Social Sciences (IPS) subjects at MAN 4 Kediri. This research uses a descriptive qualitative approach, with the data sources used being primary and secondary data sources. Data collection techniques through interviews, observation and documentation with data validity testing using triangulation. The results of the research show that the creativity provided by Social Sciences teachers in increasing students' interest in learning in Social Sciences subjects at Madrasah Aliyah Negeri 4 Kediri is quite positive, with creative learning models applied and interesting ice breaking methods provided.